Unsupervised image segmentation using Markov Random Fields - Sengur, Abdulkadir; Turkoglu, Ibrahim; Ince, M. Cevdet (Springer-Verlag Berlin, 2006)
In this study, we carried out an unsupervised gray level image segmentation based on Markov Random Fields (MRF) model. First, we use the Expectation Maximization (EM) algorithm to estimate the distribution of the input image and the number of the components is automatically determined by the Minimum Message Length (MML) algorithm. Then the segmentation is done by the Iterated Conditional Modes (ICM) algorithm. For testing the segmentation performance, we use both artificial images and real images. The experimental results are satisfactory.
14th Turkish Symposium on Artificial Intelligence and Neural Networks -- JUN 16-17, 2005 -- Izmir, TURKEY